1998
DOI: 10.1046/j.1365-2818.1998.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence of living cells

Abstract: SummaryWe have investigated the autofluorescence of viable mammalian cells (DU-145 and V79) with a confocal laser scanning microscope equipped with a UV laser. Our aim was to investigate the autofluorescence dependence on different treatments in mitochondria and lysosomes by using different reagents and to improve the confocal laser scanning microscope image quality by deconvolution. The following conclusions were drawn from the results: (1) not all of the autofluorescence comes from mitochondria; (2) one can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
131
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(144 citation statements)
references
References 9 publications
9
131
0
4
Order By: Relevance
“…On the contrary, in control cells, the discrete fluorescent sites were strongly reduced and a homogeneous fluorescence was spread in the cytoplasm. It has been demonstrated that the intracellular autofluorescent sites co-localize with mitochondria and, to a lesser extent, with lysosomes [Andersson et al, 1998]. Therefore, our findings assessed a higher content of mitochondria in the cells cultured in modeled hypogravity than in the control ones.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…On the contrary, in control cells, the discrete fluorescent sites were strongly reduced and a homogeneous fluorescence was spread in the cytoplasm. It has been demonstrated that the intracellular autofluorescent sites co-localize with mitochondria and, to a lesser extent, with lysosomes [Andersson et al, 1998]. Therefore, our findings assessed a higher content of mitochondria in the cells cultured in modeled hypogravity than in the control ones.…”
Section: Discussionmentioning
confidence: 57%
“…1.3), under 365 nm excitation from a filtered (10 nm bandwidth interference filter, 365FS10-25, Andover), high-pressure mercury lamp (HBO 100 W, Osram). The 365 nm wavelength is particularly suitable for NAD(P)H, but able to excite flavins and lipopigments too [Andersson et al, 1998]. In this way, the most important endogenous fluorophores emitting in the visible range were detected at the same time.…”
Section: Multispectral Imaging Autofluorescence Microscopy and Autoflmentioning
confidence: 99%
See 1 more Smart Citation
“…A cell's autofluorescence is indicative of the mitochondrial, cytoplasmic vesicle, nicotinamide adenine dinucleotide (NADH), and flavin content of the cell. 23,24 In this study, cytokine stimulation enhanced Cytokine-induced immunoregulatory properties JL Banyer et al the level of autofluorescence from the cells compared with the GM-CSF progenitor cells. This is likely to reflect the increased vacuole and exosome content of the cells as detected by TEM analysis.…”
Section: Ifn-c and Il-4 Differentially Effect The Morphology Of The Mmentioning
confidence: 64%
“…The mechanisms responsible for the larger amount of auto-fluorescence in the notochordal-like cell population are unknown, but they may be related to the presence of large vacuoles [22] or inclusion bodies [12] uniquely identified in this cell population. The auto-fluorescence from the endogenous intracellular coenzyme NAD(P)H and the oxidized lipid or flavoprotein has also been used to image living cells [2], as well as to distinguish normal and tumor cells [3]. The FACS protocol used here Nd not detected, › higher than AF cells, fl lower than AF cells S309 combined sorting methods by both cell size and autofluorescence, as size was believed to be an important distinguishing feature of notochordal-like cells based on prior knowledge.…”
Section: Discussionmentioning
confidence: 99%